SURPLUS RESERVES. - Miller, Herbert E. (The Accounting Review, 1947)
Abstract The article presents information about surplus reserves. In recent years, published statements have reflected a rather significant expansion in the use of those reserve accounts which are typically presented either within the net worth section or immediately above that section under a "Reserves" caption. In an attempt to acquire an impression of their nature, a number of these reserve accounts were analyzed. For this purpose, the financial statements of ninety-three business corporations, filed with the Securities and Exchange Commission during the six-year period 1937-1942, were examined. No attempt was made to select a "normal" period. However, it did seem desirable to include several pre-war years. The ninety-three companies selected for analysis are among the largest business corporations in terms of total assets, accounting for approximately 30% to 35% of the total assets in the manufacturing, trade and service industries. This bias toward size is believed to be justified because the statements of larger corporations are frequently used as examples of acceptable accounting practices and in this way exert an influence on corporate accounting.